2015
DOI: 10.1002/dta.1828
|View full text |Cite
|
Sign up to set email alerts
|

The influence of exercise and dehydration on the urine concentrations of salbutamol after inhaled administration of 1600 µg salbutamol as a single dose in relation to doping analysis

Abstract: The present study investigated the influence of exercise and dehydration on the urine concentrations of salbutamol after inhalation of that maximal permitted (1600 µg) on the 2015 World Anti-Doping Agency (WADA) prohibited list. Thirteen healthy males participated in the study. Urine concentrations of salbutamol were measured during three conditions: exercise (EX), exercise+dehydration (EXD), and rest (R). Exercise consisted of 75 min cycling at 60% of VO2max and a 20-km time-trial. Fluid intake was 2300, 270,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
62
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(69 citation statements)
references
References 30 publications
5
62
1
Order By: Relevance
“…Although several studies have investigated urine concentrations of salbutamol with respect to doping analysis (Ventura et al., ; Pichon et al., ; Sporer et al., ; Haase et al., ), pharmacokinetic data on terbutaline are insufficient. Elers et al.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Although several studies have investigated urine concentrations of salbutamol with respect to doping analysis (Ventura et al., ; Pichon et al., ; Sporer et al., ; Haase et al., ), pharmacokinetic data on terbutaline are insufficient. Elers et al.…”
mentioning
confidence: 99%
“…Usually an athlete, who uses beta 2 ‐agonist, will inhale the active substance before competition and training as prophylaxis against bronchoconstriction (Arie, ; Price et al., ). In previous studies, it has been shown that exercise modifies pharmacokinetics of drugs (Kamimori et al., ; Khazaeinia et al., ), including beta 2 ‐agonists (Schmekel et al., ; Haase et al., ). Furthermore, exercise‐induced sweating affects hydration status.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[27,[32][33][34] Significantly, a Danish group reported a subject exceeding the 1000 ng/mL threshold after only 800 μg of inhaled salbutamol but the concentration fell to only 661 ng/mL if the urinary SG was corrected to 1.020. salbutamol, in that urine and hence demands a TUE for that substance.…”
Section: Pharmacokinetic Studymentioning
confidence: 99%
“…There is no doubt that urinary thresholds and decision limits for salbutamol and formoterol introduced by WADA is an innovative way to avoid excessive use by athletes and to lessen the economic burdens associated with TUE applications. Despite this, urine thresholds can be problematic and athletes should be aware that severe dehydration during and after exercise have been shown to increase the risk of exceeding the urine threshold for salbutamol following inhalation 6 7. With terbutaline, the lack of a urinary threshold and decision limit means that an athlete can administer either oral or supratherapeutic inhaled doses with impunity as long as there is a current TUE.…”
Section: Dosing and Urine Thresholdsmentioning
confidence: 99%